1994
DOI: 10.1093/jnci/86.7.539
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Regression of Cervical Intraepithelial Neoplasia II (Moderate Dysplasia) With Topically Applied All- trans -Retinoic Acid: a Randomized Trial

Abstract: A derivative of vitamin A can reverse or suppress an epithelial preneoplasia, lending further support to the notion that chemoprevention of human cancer is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(109 citation statements)
references
References 0 publications
3
106
0
Order By: Relevance
“…The first goal of our cancer chemoprevention trials was to define a dose of DFMO that was both safe and effective. Our dose de-escalation studies and subsequent randomized placebo-controlled studies demonstrated that oral doses of DFMO between 0.25 and 0.5 g/m 2 /day for times as short as 1 month and as long as 1 year were effective in reducing rectal polyamine content in humans [85][86][87] . These studies also demonstrated that these doses, which can reduce rectal polyamine levels, did not produce detectable toxicities in excess of those observed in the group receiving placebo.…”
Section: Box 3 | Measuring Polyamine Variables In Clinical Studiesmentioning
confidence: 71%
See 1 more Smart Citation
“…The first goal of our cancer chemoprevention trials was to define a dose of DFMO that was both safe and effective. Our dose de-escalation studies and subsequent randomized placebo-controlled studies demonstrated that oral doses of DFMO between 0.25 and 0.5 g/m 2 /day for times as short as 1 month and as long as 1 year were effective in reducing rectal polyamine content in humans [85][86][87] . These studies also demonstrated that these doses, which can reduce rectal polyamine levels, did not produce detectable toxicities in excess of those observed in the group receiving placebo.…”
Section: Box 3 | Measuring Polyamine Variables In Clinical Studiesmentioning
confidence: 71%
“…'Proof of principle' for chemoprevention of cancer in humans has been established [85][86][87] . However, toxicity has abrogated the widespread adoption of agents, such as retinoids, for the prevention of cervical and oral cancers 89 .…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Cancer of the cervix, which develops in a multistep fashion through progressive intra-epithelial neoplasia (CINI-III) is another logical candidate for a chemoprevention approach. Topical application of ATRAinduced regression in 43% of patients with moderate dysplasia (CIN II) in comparison to a spontaneous regression in 27% of patients treated with placebo, but had no effect on more severe dysplasia (Meyskens et al, 1994). Moreover, N-(4-ethoxycarbophenyl) retinamide decreased the incidence and increased survival in a population at high risk of oesophageal cancer (Han, 1993), but retinoids have had consistently no effect on reversal of bronchial metaplasia (Lee et al, 1994).…”
Section: Clinical Datamentioning
confidence: 99%
“…Other successful retinoid trials have been reported, including cervical dysplasia (20) and xeroderma pigmentosum (21). Treatment with all-trans-retinoic acid is a relatively standard therapy for the treatment of acute promyelocytic leukemias (22).…”
Section: Introductionmentioning
confidence: 99%